Defect‐Laden MoSe2 Quantum Dots Made by Turbulent Shear Mixing as Enhanced Electrocatalysts. Issue 27 (24th May 2017) - Zhu, Chongyang; Huang, Yuan; Xu, Feng; Gao, Peng; Ge, Binghui; Chen, Jing; Zeng, Haibo; Sutter, Eli; Sutter, Peter; Sun, Litao
Abstract : A high density of edge sites and other defects can significantly improve the catalytic activity of layered 2D materials. Herein, this study demonstrates a novel top‐down strategy to maximize catalytic edge sites of MoSe2 by breaking up bulk MoSe2 into quantum dots (QDs) via "turbulent shear mixing" (TSM). The ultrasmall size of the MoSe2 QDs provides a high fraction of atoms in reactive edge sites, thus significantly improving the catalytic activities. The violent TSM further introduces abundant defects as additional active sites for electrocatalytic reactions. These edge‐proliferated and defect‐laden MoSe2 QDs are found to be efficient electrocatalysts for the hydrogen evolution reaction, and useful as counter electrodes in dye‐sensitized solar cells. The work provides a new paradigm for creating edge‐proliferated and defect‐rich QDs from bulk layered materials. Abstract : "Turbulent shear mixing" is utilized to maximize catalytic sites of MoSe2 by breaking up the bulk counterpart into defect‐laden quantum dots, which demonstrate enhanced electrocatalytic activities in hydrogen evolution reaction and toward the reduction of I3 − in dye‐sensitized solar cells.